Engleski - MILOJEVIĆ, Stefan; MATEJIĆ, Tijana; MILOŠEVIĆ, Miloš; RESIMIĆ, Milan (Journal of process management and new technologies, 2025)
Aksoy, T., & Uzay, S. (2021). Relationship between Fraud auditing and Forensic accounting. In Auditing Ecosystem and Strategic Accounting in the Digital Era: Global Approaches and New Opportunities (pp. 127-146). Cham: Springer International Publishing. Bartlett, M. S. (1950). Tests of significance in factor analysis. British Journal of Psychology, 3(2), 77–85. https://doi.org/10.1111/j.2044-8317.1950.tb00285.x Boone, H. N., & Boone, D. A. (2012). Analyzing Likert data. Journal of Extension, 50(2), 1–5. Cattell, R. B. (1966). The scree test for the number of factors. Multivariate Behavioral Research, 1(2), 245–276. https://doi.org/10.1207/s15327906mbr0102_10 Chetry, P., Tiwari, R. K., Baxi, J., & Shekar, M. C. (2025). Student Perspectives on Forensic Accounting in Indian Higher Education. Vision, 09722629241307135. Costello, A. B., & Osborne, J. W. (2005). Best practices in exploratory factor analysis: Four recommendations for getting the most from your analysis. Practical Assessment, Research, and Evaluation, 10(1), 7. https://doi.org/10.7275/jyj1-4868 DeVellis, R. F. (2016). Scale Development: Theory and Applications (4th ed.). SAGE Publications. Field, A. (2018). Discovering Statistics Using IBM SPSS Statistics (5th ed.). SAGE Publications. Hermiyetti, H. (2025). The role of forensic accounting in detecting and investigating cases of corporate financial fraud. INJOSEDU: International Journal of Social and Education, 2(3), 603-613. Kaiser, H. F. (1960). The application of electronic computers to factor analysis. Educational and Psychological Measurement, 20(1), 141–151. https://doi.org/10.1177/001316446002000116 Kaiser, H. F. (1974). An index of factorial simplicity. Psychometrika, 39(1), 31–36. https://doi.org/10.1007/BF02291575 Kayed, D., & Al-Sartawi, A. (2024). Forensic accounting and big data a literature paper. In Artificial Intelligence-Augmented Digital Twins: Transforming Industrial Operations for Innovation and Sustainability (pp. 303-312). Cham: Springer Nature Switzerland. Kramer, B., Seda, M. and Bobashev, G. (2017). Current opinions on forensic accounting education. Accounting Research Journal, 30(3), 249-264. https://doi.org/10.1108/ARJ-06-2015-0082 Lakshmi, P., & Menon, G. (2016). Forensic accounting: A checkmate for corporate fraud. Journal of Modern Accounting and Auditing, 12(9), 453-460. Nunnally, J. C., & Bernstein, I. H. (1994). Psychometric Theory (3rd ed.). McGraw-Hill. Prabhudesai, S. B., & Kamat, M. A. (2025). Challenges before Forensic Accounting in Industry 5.0. Transforming India’s Future: Accounting, Management & Commerce for Sustainable Industry 5.0 e-Book ISBN: 978-81-968645-2-1, pp. 496-503. Vutumu, A. (2024). Building the Foundation: Towards a Theoretical Framework for Forensic Accounting. International Journal of Accounting, Finance and Risk Management, 9(4), 131-141.